If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(9 + 4x) = -106 (9 * -2 + 4x * -2) = -106 (-18 + -8x) = -106 Solving -18 + -8x = -106 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -8x = -106 + 18 Combine like terms: -18 + 18 = 0 0 + -8x = -106 + 18 -8x = -106 + 18 Combine like terms: -106 + 18 = -88 -8x = -88 Divide each side by '-8'. x = 11 Simplifying x = 11
| f(89.25)= | | 8a^3=8a | | 7r^2=175r | | 6x^2=-7 | | (4x+5)(x-7)=8x+10 | | x^2-10+15=0 | | 4y^2+100=0 | | (2x+4)+(3x-8)= | | 10+3(k-2)= | | X-.1=40 | | Tanx=15/15 | | 3x+4(2x-1)=x-4 | | w(a+6)+2w= | | 1517356884191*x+6173920479630499*y=1 | | y^2+2y-y^2=0 | | 64=y(y)+42y | | 6m+4(3+2m)= | | 2y+ix=4+x-i | | (x+1)(x+2)(x+3)(x+4)+8=0 | | 0.5p+10+1.5p=20 | | 3x+30+42=180 | | 2(x-1)+x=-17 | | 5/9(F-32)=-20 | | 16x^2+31x-14=0 | | 10x^2+31x+4=18 | | 10-2(3-6x)=3(2x-4) | | 3d+e=26 | | 12x+20=2x | | 2d-9e=-2 | | c=6a-3b-1 | | c=6a-3b | | 2(b-1)=6 |